Synthesis of doped Co based perovskite and photocatalytic degradation of organic wastewater - XIE He; TANG Bin; CHEN Bingbing; LI Jiali; ZHAN Haijuan (Gongye shui chuli)
Cobalt-based perovskite catalysts doped with Ce and Mn were synthesized by sol-gel method using metal nitrate as raw materials. The structural properties of the prepared catalysts were investigated by XRD, SEM, TEM, XPS, EPR, etc. The photocatalytic degradation performance under xenon lamp conditions was investigated by using alizarin red and acid fuchsin as probe organic pollutants. The degradation rates of alizarin red and acid fuchsin could reach 95% and 90%, respectively, and the catalyst maintained good degradation stability after being recycled for 6 times. The results showed that the introduction of Mn and Ce elements increased the specific surface area of LaCoO3-based perovskite, and more structural defects were formed in the crystal structure. XPS, ERP and infrared tests before and after the reaction showed that the oxygen vacancy defect in the material structure could promote the collapse of the quinone structure in the red structure of the material, and further improved the photocatalytic degradation performance. At the same time, surface oxygen species and oxygen vacancy were the main active species for photocatalytic degradation of organic pollutants, and LaCo0.7Ce0.3O3 showed the best photocatalytic degradation performance due to its suitable structural properties.